Developments of Low-Cost Procedure to Estimate Cloud Base Height Based on a Digital Camera - Janeiro, Fernando M. (2010)
Cloud height, wind speed and direction at cloud height play an important role in air safety. This paper presents a low-cost system based on digital cameras to estimate cloud base height. It is shown that both wind speed and direction can also be obtained with this system. The method is based on triangulation and uses image registration to identify common cloud features in photographs taken from different positions. The wind speed and direction is obtained from two time-lapsed pictures taken from the same position. The measurement results are compared with LIDAR measurements performed on site.